PERSEPSI WISATAWAN TERHADAP PANTAI NUSA DUA - Ni Luh Gde Sri Sadjuni (Institut Pariwisata dan Bisnis Internasional, 2014)
The attraction offered by Bali as a tourist destination belle hospitality not only residents, but also the unique culture and customs and natural beauty, especially the beautiful beach with the waves and sunset or sunrisenya. From the point of view of tourists, especially domestic tourists, the beach becomes a part of the most interesting attractions. Various activities can be done in coastal areas, such as sport exercise, swimming, relax have fun, selling or other types of work. However, the issue regarding the reclamation plan Nusa Dua area, has led to a prolonged conflict plaguing the society Nusa Dua, also the tourists themselves. Various growing perception among tourists on the beach of Nusa Dua. This study aimed to measure the perception of tourists further aspects: attractions, facilities / amenities, accessibility, and service as a tourist attraction Nusa Dua beach, so as to provide an overview of the situation and the condition of the beach in the eyes of tourists. Â Qualitative and quantitative data were collected by the method of observation, interviews and questionnaires were accidental sampling and purposive sampling of 110 domestic tourists visiting the beach of Nusa Dua.Â The results showed that: From the aspect Attractions, sub aspect is the highest waves, followed by sub Cleanliness, neatly arranged area and winds were calm. From the aspect of accessibility highest sub aspect is that information is readily available, the next is the Roads and Transport. Aspects of Amenities, sub aspects Toilet highest, followed by sub-Trash, Telecommunications, Parking, and Souvenir. While the service aspect, the highest sub-aspect is Information, the next is the sub aspects Life Guard and sub aspects of Hospitality.